The Protective Effect of Poloxamer-188 on Platelet Functions. (November 2017) - Guler, Nil; Abro, Schuharazad; Emanuele, Marty; Iqbal, Omer; Hoppensteadt, Debra; Fareed, Jawed
Background: Poloxamer-188 (MST-188) is effective in the repair/recovery of damaged cell membranes. MST-188 is a promising agent for protecting blood cell viability. The aim of the study is to test the hypothesis that MST-188 can extend the duration of platelet function. Materials and Methods: Blood samples were collected from 20 healthy volunteers. MST-188 (10 or 2 mg/mL) containing platelet-rich plasma (PRP) was prepared with 2 procedures. First, PRP prepared from MST-188 added whole blood (WB); second, MST-188 was added to PRP. These were referred to MST-188-WB preparation (WBP) and MST-188-PRP preparation (PRPP), respectively. For control, saline was used in the same manner. Agonist-induced aggregation (AIA) studies were performed at 30, 180, and 300 minutes using Platelet Aggregation Profiler (PAP-8) aggregometer (Bio/Data Corporation, Horsham, Pennsylvania) and Adenosine diphosphate (ADP), arachidonic acid, collagen, and epinephrine as agonists at final concentration of 20 µM, 500 µg/mL, 0.19 mg/mL, and 100 µM, respectively. Results: There was a protective effect of MST-188 on ADP and collagen AIA. At 300 minutes, ADP AIA was found to be 50.2% higher than saline control in 2-mg WBP, 43% at 10-mg PRPP, and 10.4% at 2-mg PRPP. Protective effect of on collagen AIA was 65.9% in 2-mg WBP, 42.74% at 10-mg PRPP, and 11.42% at 2-mg PRPP. In comparison between 30 and 300 minutes, MST-188 showed significant protection in terms of ADP and collagen receptors and for both types of preparations (WBP and PRPP). Conclusion: The protective effects of MST-188 on ADP- and collagen-induced platelet aggregation may contribute to the preservation of platelet functionality upon storage in blood banks.